Mizuko Kuyō and New Age Concepts of Reincarnation - Komatsu, Kayoko (Japanese journal of religious studies, 2003)
This essay is an attempt to apply the religious views of people who follow New Age ideas, based on particular beliefs concerning reincarnation, to the question of abortion and memorial rites for the aborted. The performance of mizuko kuyō 水子供養 (memorial rites for aborted or stillborn children) expanded dramatically from the 1970s. Two of its characteristics are the threat of a curse from the aborted fetus, and sexual discrimination based on fixed gender roles. The performance of these rites has spread, however, without any religious answers to questions concerning the meaning of abortion and when life begins and ends. In contrast, the idea of reincarnation, which sees life in this world as continuing from past lives and into the present and future lives, offers a new perspective to the act of abortion as a choice involving human relationships for the fetus and the mother who bears it. In this article I present the findings of a survey of people whose ideas on life are based on New Age beliefs of reincarnation, and show how these beliefs allow them to accept the experience of abortion as women and offer support to continue their lives in a positive way.